Nutrition and production of Helianthus annuus in a function of application of leaf silicon - Flores, Rilner Alves; Arruda, Everton Martins; Souza Junior, Jonas Pereira de [UNESP]; Prado, Renato de Mello [UNESP]; Alves dos Santos, Ana Carla; Aragao, Amanda Sasamoto; Pedreira, Nicolas Gomes; Costa, Cinthya Freitas da (Taylor & Francis Inc, 2019)
Silicon (Si) is important as it increases plant tolerance to abiotic stresses. However, studies on in foliar fertilization are still scarce. The objective of this research was to evaluate the effect of foliar application of silicon on nutrition and production of Helianthus annuus. The study was carried with a completely randomized design, consisting of five doses of silicon (0; 0.84; 1.68; 2.52 and 3.36 mg L-1) applied as silicate, with four replicates. Biometric evaluations and relative chlorophyll index (RCI) measurements were performed, being also observed the dry matter production and the silicon use efficiency by plants. The RCI is not affected by the foliar application of Si, while the height and leaf area increase by 8.3 and 25.4%, respectively. Foliar Si application up to the dose of 3.36 g L-1 promotes linear increases in the dry matter production of shoots (32%), capitulum (19%) and the whole plant of sunflower (27%).
Keywords: plant nutrition; sunflower; nutritional efficiency; fertilizers; leaf silicate